SOSIOLINGUISTIK: TEORI, PERAN, DAN FUNGSINYA TERHADAP KAJIAN BAHASA SASTRA - Abdurrahman, Abdurrahman (Laboratorium Informasi & Publikasi Fakultas Humaniora UIN Maulana Malik Ibrahim Malang, 2008)
Sosiolinguistics is a study of language character, language variation, function of language, and language use in interaction and the language function in society. Language for a man of letters is a media to express ideas and present specific messages to society. These ideas come from intuition, imagination, and a man of letters personal experiences of in his society. The goal of sociolinguistics in language literature discussion is to give a description of the social condition of a society related to its language.